The Charecteristics of Science in Information Society - Augustinaitis, Arūnas (Sociologija. Mintis ir veiksmas, 1998)
The article discusses whether and to what extent the sciences are postmodern without considering the meaning and implications of the notion of postmodernity. Arguably, the post-industrial science is postmodern by itself just because it is defined by the paradigm of information. Science is the quintecence of postmodernity and provides the basis of informational existence of postmodern society. In other words, science is a source and medium of post-modernity. Informational science grounds its own rules and makes a link between philosophy and knowledge, connects the boundedlessness of methaphilosophical language games (Lyotard) with the transinformational theory. While the transinformational theory suggests traditional philosophical problematique, informational science creates a novel postmodern epistemology.